The Risk Factors of Bacterial Meningitis in Late-Onset Neonatal Sepsis - Noviyani, Ni Made Reditya; Kardana, I Made; Mahalini, Dewi Sutriani; Suparyatha, Ida Bagus Gede; Ariawati, Ketut; Nilawati, Gusti Ayu Putu; Sukmawati, Made (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Neonatal bacterial meningitis has a significant contribution on neonatal morbidity and mortality. It is the most common complication of late-onset neonatal sepsis. An understanding of the risk factors for bacterial meningitis in late-onset neonatal sepsis is required to provide comprehensive management. AIM: To identify the risk factors of bacterial meningitis in late-onset neonatal sepsis. METHODS: This is an analytical study with a case–control design, conducted in May 2019-February 2021, involving neonates aged 4–28 days who suffered from late-onset neonatal sepsis in Level II and III Neonatal Care Unit, Sanglah General Hospital Denpasar. Statistical analysis was performed using Chi-square and logistic regression. RESULTS: A total of 54 patients were analyzed in this study. The mean age of subjects with neonatal bacterial meningitis was 13 days and the majority of them were male (51.9%). The risk factor of bacterial meningitis in late-onset neonatal sepsis was gestational age <37 weeks with odds ratio 4.22 (95% confidence interval 1.28–13.86, p = 0.01). There was no significant association of birth weight <2500 g, neonatal asphyxia, and invasive procedure on neonatal bacterial meningitis. CONCLUSION: Gestational age <37 weeks is a risk factor for bacterial meningitis in late-onset neonatal sepsis.